Isolation, characterization and x-ray structure determination of 2,5-bis(4-methylbenzylthio)-1,3,4-thiadiazole - Tayamon, Shahedeh; Tiekink, Edward R. T.; Nikpour, Farzad; S. A. Ravoof, Thahira Begum; Mohamed Tahir, Mohamad Ibrahim; Karen, Anne Crouse (Springer, 2014)
The reaction of hydrazine hydrate with carbon disulfide and 4-methylbenzyl chloride in basic solution yielded 2,5-bis(4-methylbenzylthio)-1,3,4-thiadiazole (C18H18N2S3, compound 1) in addition to the expected S-4-methylbenzyldithiocarbazate. The molecule has approximate twofold symmetry with the C=S bond lying on the pseudo axis. The five membered ring is planar with the three S atoms mutually syn, and with pendent 4-methylbenzylthio substituents; the dihedral angle between the terminal rings is 52.21(7)°. The compound 1 crystallizes in the triclinic space group \(P\bar{1}\) with a = 6.0139(3) Å, b = 11.8694(7) Å, c = 12.6330(7) Å, α = 72.583(5)°, β = 82.827(4)°, γ = 89.882(4)° and Z = 2.